Effect of Stress Level on Retrofitting of Exterior Beam Column Joints - Bhandari, Puneet (My University, 2010)
Almost all the structures whether industrial, commercial or housing are constructed of RCC. There structures fare nicely under normal circumstances, but in the event of major earthquakes, higher load imposition etc. they may suffer permanent damage. This poses a more difficult scenario for a structural engineer than constructing a new building. This is due to number of restraints an already constructed building throws up like non engineered construction, wear & tear etc. Instead of tearing apart the structure one can strengthen the deficient structural elements of the structure. Thanks to the advancement in technology with the help of non-destructive testing one can easily identify such deficient elements. Once identified the best way out is to retrofit such elements. Retrofitting is different from repair or rehabilitation. It is basically a process of strengthening and enhancement of the performance of deficient structural elements in a structure or of the structure as whole. Retrofitting of deficient buildings can be done by increasing the strength, stiffness and/or ductility of its specific constituent elements or of the whole building. For any building, depending upon the requirement, a combination of the above may also be selected. Retrofitting of individual members or elements is referred to as local retrofitting. In this present study the effect of stress level on retrofitting of exterior beam column joints is studied. The deflections of retrofitted and non- retrofitted specimens are compared. Specimens were stressed to ultimate loading (100% damage) and the deflections were noted. After retrofitting with the ferrocement technique, the retrofitted specimens were compared with the controlled specimens. Results show that there is an increase in load carrying capacity for beam column joint retrofitted with ferrocement varying in different cases. Also increase in yield load is observed.
M.E. (Structures)
Keywords: Retrofitting; Concrete; Beam Column Joints; Stress